Altered Spontaneous Brain Activity and Network Property in Patients With Congenital Monocular Blindness - Ding, Jingwen; Qu, Xiaoxia; Cui, Jing; Dong, Jie; Guo, Jian; Xian, Junfang; Li, Dongmei (Frontiers in Neurology, 2022)
Individuals with congenital monocular blindness may have specific brain changes since the brain is prenatally deprived of half the normal visual input. To explore characteristic brain functional changes of congenital monocular blindness, we analyzed resting-state fMRI (rs-fMRI) data of 16 patients with unilateral congenital microphthalmia and 16 healthy subjects with normal vision to compare intergroup differences of amplitude of low frequency fluctuations (ALFF), functional connectivity (FC) and network topolgoical properties. Compared with the controls, microphthalmic patients exhibited significantly lower ALFF values in the left inferior occipital and temporal gyri, superior temporal gyrus, inferior parietal lobe and postcentral gyrus, whereas higher ALFF in right middle and inferior temporal gyri, middle and superior frontal gyrus, left superior frontal and temporal gyri including angular gyrus. Meanwhile, FC between left medial superior frontal gyrus and angular gyrus, FC between left superior temporal gyrus and inferior parietal lobe and postcentral gyrus decreased in the patients with congenital microphthalmia. In addition, graph theory-analysis revealed increased regional network metrics (degree centrality and nodal efficiency) in the middle and inferior temporal gyri and middle and superior frontal gyri, while decreased values in the inferior occipital and temporal gyri, inferior parietal lobule, postcentral gyrus, and angular gyrus. Taken together, patients with congenital microphthalmia had widespread abnormal activities within neural networks involving vision and language and language-related regions played dominant roles in their brain networks. These findings may provide clues for functional reorganization of vision and language networks induced by congenital monocular blindness.